2020
DOI: 10.3389/fnsys.2020.00031
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Study on Motor Control and Recovery After Stroke: Toward a Constructive Loop Between Experimental and Virtual Embodied Neuroscience

Abstract: Being able to replicate real experiments with computational simulations is a unique opportunity to refine and validate models with experimental data and redesign the experiments based on simulations. However, since it is technically demanding to model all components of an experiment, traditional approaches to modeling reduce the experimental setups as much as possible. In this study, our goal is to replicate all the relevant features of an experiment on motor control and motor rehabilitation after stroke. To t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 128 publications
(203 reference statements)
0
32
0
Order By: Relevance
“…The simplest and hence most elaborate is the Kuramoto model ( 32 ). It is widely utilized for describing emergent phenomena in complex systems ( 81 ), such as the brain ( 8284 ), with a structure often represented via complex networks ( 85 ). For synchronization at frequency Ω, the model reads ( 33 ) where θ i denotes the phase of the i- th node oscillating with a natural frequency ω i , the dependence on time is implicit, and due to the synchronization θ j ( t − τ ij ) = θ j ( t ) + Ωτ ij .…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplest and hence most elaborate is the Kuramoto model ( 32 ). It is widely utilized for describing emergent phenomena in complex systems ( 81 ), such as the brain ( 8284 ), with a structure often represented via complex networks ( 85 ). For synchronization at frequency Ω, the model reads ( 33 ) where θ i denotes the phase of the i- th node oscillating with a natural frequency ω i , the dependence on time is implicit, and due to the synchronization θ j ( t − τ ij ) = θ j ( t ) + Ωτ ij .…”
Section: Model and Methodsmentioning
confidence: 99%
“…The mouse connectome in Fig. 2 (A) was obtained from the Allen Institute Mouse Brain Connectivity data ( 37 ), which is integrated in The Virtual Mouse Brain ( 90 ), and which was already used to model mice brain dynamics ( 10, 84 ).…”
Section: Model and Methodsmentioning
confidence: 99%
“…In the field of stroke recovery, there is a need for the implementation of these closedloop systems to modulate oscillatory activity and reduce the high variation in treatment efficacy seen between patients. The recently developed "Embodied Brain" closed-loop simulation model may help us to understand the impacts of specific changes to neuronal circuits and oscillatory dynamics before implementing them experimentally (Allegra Mascaro et al, 2020). Future research should combine environmental and direct brain stimulation techniques in animal models to improve our understanding of evoked and enhanced oscillatory dynamics in order to refine the closed-loop systems used in human patients (Figure 2).…”
Section: Future Directions For Stroke Recoverymentioning
confidence: 99%
“…As a consequence in the study of its large-scale dynamics, the brain is typically represented as a network of anatomically interacting regions each constrained by inherent dynamics (Sanz-Leon et al, 2015). Using this paradigm, a number of modeling studies have demonstrated that independently of the size of the brain regions and their underlying dynamics, neuroanatomical constraints of the human brain shape and drive its functionality during resting healthy state (Kringelbach et al, 2015; Deco et al, 2009, 2011; Schirner et al, 2018; Courtiol et al, 2020), or during pathologies such as epilepsy (Jirsa et al, 2017), stroke (Allegra Mascaro et al, 2020), or Alzheimer’s disease (Stefanovski et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Functional alterations are studied through the dFC and MC, which capture temporal and spatial aspects of the FC (Arbabyazd et al, 2020). For the last part, we utilize Kuramoto oscillators, which despite being overtly simple, due to their parsimonious parametrization allow for drawing specific links between network structure and the emergent synchronization patterns of the neuronal activity (Pope et al, 2021; Cabral et al, 2011; Allegra Mascaro et al, 2020).…”
Section: Introductionmentioning
confidence: 99%